Current situation and socio-educational challenges of young afro-descendent women in the basque country - Bilbao Urquidi, Saioa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this article we focus on the reality of young Basque women of African descent, in terms of their experiences and the difficulties they encounter, based on five dimensions such as; the family and social network, education, the workplace, identity and coexistence. For this, a qualitative methodology of social research has been used. Specifically, a discretionary survey has been prepared consisting of a total sample of three discussion groups. The results of the five dimensions analyzed reflect the difficulties that these girls have to deal with in their lives.